2009
DOI: 10.1007/s11249-009-9511-x
|View full text |Cite
|
Sign up to set email alerts
|

Tribochemical Behavior of Si3N4–hBN Ceramic Materials with Water Lubrication

Abstract: The main objective of this article is to study the tribological behavior of Si 3 N 4 -hBN composites with different hexagonal boron nitride (hBN) volume fraction under distilled water lubrication. Water-lubricated sliding tests were carried out on a pin-on-disc tester, and Si 3 N 4 was used as friction pair. The results showed that the addition of hBN to Si 3 N 4 resulted in a severe decrease of the friction coefficient, from 0.35 for Si 3 N 4 against Si 3 N 4 to 0.01 for Si 3 N 4 -20% hBN against Si 3 N 4 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…When the speed was 1.73 m/s and a load of 10N in dry friction conditions, the friction coefficient measured was around 0.12 for the Si 3 N 4 -10 vol% hBN/ASS (austenitic stainless steel) tribopair [16,17]. However, in drip-feed water lubricating condition, the friction coefficient of Si 3 N 4 -20 vol% hBN decreased from 0.35 to 0.01 [18]. Furthermore, with the increase of hBN to 10 vol% at a relative humidity RH of 55~65%, the friction coefficient and wear rate were further reduced respectively to 0.03 and 10 −6 mm 3 /Nm [19,20].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…When the speed was 1.73 m/s and a load of 10N in dry friction conditions, the friction coefficient measured was around 0.12 for the Si 3 N 4 -10 vol% hBN/ASS (austenitic stainless steel) tribopair [16,17]. However, in drip-feed water lubricating condition, the friction coefficient of Si 3 N 4 -20 vol% hBN decreased from 0.35 to 0.01 [18]. Furthermore, with the increase of hBN to 10 vol% at a relative humidity RH of 55~65%, the friction coefficient and wear rate were further reduced respectively to 0.03 and 10 −6 mm 3 /Nm [19,20].…”
Section: Introductionmentioning
confidence: 97%
“…In the case a B 4 C ceramic matrix after adding hBN, the friction coefficient lowered from 0.373 for the B 4 C/B 4 C tribopair to 0.005 for the B 4 C-20 wt% hBN/B 4 C tribopair in water lubricating condition [15]. In our previous research [16][17][18][19][20], we studied the tribological performances of Si 3 N 4 -hBN bearing on stainless steel at different sliding speeds and with a normal load. When the speed was 1.73 m/s and a load of 10N in dry friction conditions, the friction coefficient measured was around 0.12 for the Si 3 N 4 -10 vol% hBN/ASS (austenitic stainless steel) tribopair [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The authors also found that the friction coefficient was not influenced by BN addition to Si 3 N 4 /BN composites. However, our previous research showed that Si 3 N 4 /BN composites (micro-sized) showed better tribological properties [10][11][12][13][14]. Especially, a lower friction coefficient (0.03) and wear rates of order 10 -6 were obtained for a sliding pair of Si 3 N 4 /BN composite and stainless steel, which is attributed to the formation of a self-lubricating film composed of SiO 2 , H 3 BO 3 and Fe 2 O 3 .…”
Section: Introductionmentioning
confidence: 95%
“…Nevertheless, the introduction of the lubricating phase severely destroys the continuity of the ceramic phase, thus resulting in a large amount of defects. The intrinsic brittleness of ceramics and extremely sensitivities to the presence of defects lead to poor mechanical properties of the ceramics, which subsequently limit the application of such kind of materials as wear‐resistance components in harsh working conditions.…”
Section: Introductionmentioning
confidence: 99%